(3x^2-2x+4)+(5x^2+6x-8) - Combine like terms
8x^2+4x-4
(f+g)(x)=8x^2+4x-4
Answer:
6
Step-by-step explanation:
b = 2 units
h = 6 units
A=1/2 *b*h
= 1/2 *6*2
= 6
Answer:
I think it is 2 one
Step-by-step explanation:
Answer:
The Pythagorean theorem is a form of equation when dealing with the 3 sides of a right triangle. The formula is a^2 + b^2 = c^2. c^2 would be the side that equals the same amount of the other sides combined. Or a hypotenuse.
Note:
Hope this helps! Good Luck!
<em>-kiniwih426</em>